PENGARUH PENGGUNAAN PUPUK DARI LIMBAH RUMPUT LAUT TERHADAP PERTUMBUHAN TANAMAN BAYAM - Wahyudi, Rezky; Wijaya, Mohammad; Sukainah, Andi (Universitas Negeri Makassar, 2018)
This study aims to determine the effect of using seaweed waste fertilizer on the growth of spinach plants consisting of stem height, number of leaves, and leaf length. This study uses Completely Randomized Design (CRD) with media of seaweed waste concentration 25%, 30%, and 65%. Data were analyzed by variance (ANOVA) and continued with DMRT further testing. The results of this study indicate that the concentration of seaweed waste has a significant effect on changes in stem height, leaf number and leaf length which is the best treatment of soil concentration with seaweed waste is a concentration of 75-25% and shows 100% percentage of life.